Answer:
Step-by-step explanation:
f(x) = 3x + 1 and g(x) = x^2 - 6
(f + g) (x)
(3x + 1) + (x^2 - 6)
3x + 1 + x^2 - 6
3x - 5 - x^2
=> -x^2 + 3x - 5
I hope this helps!
16 times the square root of x:
16 * √x so f(x) = 16√x
Answer:
The answer to this question is graph B
I think, the answer will be -7
We have:
f(x)=1/(x-2)
g(x)
Then:
(fg)(x)=[1/(x-2)](g(x))=g(x)/(x-2)
Now; we calculate: (fg)`(x)
Remember: (u/v)=(u`v-vu´)/v²
Therefore:
(fg)´(x)=[g´(x)*(x-2) - 1*g(x)]/ (x-2)²
We know that:
g´(1)=-1
(fg)´(1)=6
Therefore:
6=[-1*(1-2)-g(1)]/(1-2)²
6=[1-g(1)]/1
6=1-g(1)
-g(1)=6-1
g(1)=-5
Answer: B. -5